Inhibitory Effect of Curcumin-Cu(II) and Curcumin-Zn(II) Complexes on Amyloid-Beta Peptide Fibrillation - Rona Banerjee (Bioinorganic Chemistry and Applications)
Mononuclear complexes of Curcumin with Cu(II) and Zn(II) have been synthesized and, characterized and their effects on the fibrillization and aggregation of amyloid-beta (Aβ) peptide have been studied. FTIR spectroscopy and atomic force microscopy (AFM) observations demonstrate that the complexes can inhibit the transition from less structured oligomers to β-sheet rich protofibrils which act as seeding factors for further fibrillization. The metal complexes also impart more improved inhibitory effects than Curcumin on peptide fibrillization.